Chapter 27 Repeatability versus Unrepeatability in Free Improvisation - Gartmann, Thomas (Taylor & Francis, 2021)
The idea of improvisation, broadly defined, has been integral to our imagination of the medieval musical past. It can be related to many elements of production: to the act of un-notated creation; to the manipulation and amplification of notated materials; to our observance of rigid rules and formulae; or to spontaneous freedom. Likely a product of the Carolingian Renaissance, this is the first medieval music treatise to address an aspect of chant performance that does not only relate to a memorized repertoire, but includes an unwritten practice of extemporizing an accompanying voice to a pre-given melody. The art of "coloration" or the ornamentation of a line, whether polyphonic or monophonic, had been an integral part of extemporization since at least the time of the Ad organum faciendum treatises. When planning author's ontological inquiries, the author's would do well to remember the possible existence of creativity that is not inspired, or ephemerality that is not performer- or expression-centered.